New Approach to Sugar Dienes; Useful Building Blocks for the Synthesis of Bicyclic Derivatives - Witkowski, Grzegorz; Jarosz, Sławomir (Synlett, 2013)
A sugar aldehyde with silyl protection at C1, readily prepared from methyl α-d-glucopyranoside, reacted with allylborate or allylchromium reagents to afford the corresponding (anti) adducts, which were selectively converted into either E- or Z-diene. Deprotection of the anomeric position with TBAF proceeded in excellent yield, and further functionalization of the resulting hemiacetal led to the formation of complex bicyclic products such as highly functionalized oxazolidines.
Keywords: carbohydrates; chiral pool; cycloaddition; stereoselective synthesis; protecting groups